Labour in Vietnam - Chan, Anita (Book collections on Project MUSE., 2011)
Two decades after Vietnam introduced a programme of economic renovation commonly known in Doi Moi, the country today allows market competition in industry, and a new working class has been created. This is the first book to focus on the role and conditions of workers in the new economic regime. The authors of the book trace Vietnam's labour history, explore the impact of the socialist legacy and examine the reasons for the large number of recent strikes. The book provides insights into the workforce of one of Asia's most rapidly developing industrial economies.